Soil Ba, Cd, Co, Cr, Cu, Ni, Mn, Pb, and Zn contents in the Basaltic Hillsides of Santa Catarina, Brazil - Guilherme de Lima Steffens; Daniely Neckel Rosini; Ilana Marin Suppi; Elias da Silva Scopel; Letícia Cristina de Souza; Jaime Antônio de Almeida; David José Miquelluti; Rogério Laus; Mari Lucia Campos (Ciência Rural)
ABSTRACT: The Basaltic Hillsides region spans a vast area in western Santa Catarina State, Brazil, consisting of magmatic flows from the Serra Geral Group. This study analyzed soil levels of Ba, Cd, Ni, Cu, Zn, Cr, Pb, Mn, and Co in these hillsides, comparing them to the reference values set by current legislation for Santa Catarina. Pearson correlation analysis and hierarchical dendrogram were conducted based on results frommultiple studies employing consistent methodologies. Nearly all trace elements showed levels above the Quality Reference Values (QRVs), except for Pb. The difference between current QRVs and natural backgroundlevelshighlights the need to update Ordinance IMA/SC n° 45/2021 to establish specific QRVs for the Basaltic Hillsides of Santa Catarina.